Ureteral Embolization to Prevent Thrombotic Obstruction of Nephrostomy Catheters in the Context of Refractory Hemorrhagic Radiation Cystitis with Severe Vesicoureteral Reflux - Vidhush Yarlagadda; Keith Pettibon; Nathan Ertel; Jeffrey Nix (Case Reports in Urology)
We present a case of refractory hemorrhagic radiation cystitis in a patient who failed conservative management and was unable to undergo operative urinary diversion secondary to multiple comorbidities. His management was complicated by recurrent obstruction of his nephrostomy catheters due to marked ureteral thrombus formation from blood refluxing into the ureters from the urinary bladder. We were successful in treating his condition by occluding his distal ureters with a combination of embolization coils and glue to prevent the reflux of blood in order to allow his nephrostomy catheters to function properly.